Strategi Fundraising Program Gerakan Koin Nu di Upzis Nu Care Lazisnu Kabupaten Purbalingga - Nur Lelaelisa, Nur Lelaelisa (Mabsya: Jurnal Manajemen Bisnis Syariah, 2023)
Fundraising is the collection of funds sourced from the community both the upper and lower middle class. One of the fundraising programs is the Upzis NU Care Lazisnu Coin movement program Purbalingga Regency. The NU Coin Movement program is one the programs where the NU Coin movement is carried out by collecting small change which is put in cans in each branch to be deposited every month. He Strategy Fundraising for the NU Coin movement program at the Upzis NU Care Lazisnu institution Purbalingga Regency is carried out to increase the amount of NU Coin funds each year as well as the strategy at the Upzis NU Care Lazisnu institution in Purbalingga Regency it runs more effectivel. This type of research is qualitative research namely research that produces descriptive date in the form of written or spoken words from people and observed behavior. In this way researchers find out data on the acquisition of NU Coins spread across 18 sub district in Purbalingga Regency. With the aim of knowing the results obtained from the NU Coin program. The purpose of this study was to find out how the fundarising strategy of the NU Coin movement program and qualitative factors types of field research factors and obstacles fced by Upzis NU Care Lazisnu Purbalingga Regency in collecting NU Coins. By using the method (field research). The data used are primay and secondary daya by collecting data from observations, interviews, and documentation. Based on the results of the fundarising strategy carried out by Upzis NU Care Lazisnu Purbalingga Regency reseachs found that Upzis NU Care Lazisnu Purbalingga Regency is it open to munfiq (people who donate) in managing NU Coin funds obtained the more funds are channeled to feel the benefit of the people. And the collection of Nu Coins divided by 50% for Nu branches, 22,5% for Upzis, and 27,5% deposited in Upzis NU Care Lazisnu Regency.